Analysis of Movement on Growing “Budi Pekerti” (Character) Based on Multiculturalism at Primary Schools - Agusniati, Andi (Green Publisher Indonesia, 2023)
This study aimed at exploring and identifying the points of conceptual action of the Movement on Growing the ‘Budi Pekerti’ (Character) based on Multiculturalism. The type of this research was Qualitative Research, with linear and sequential activities through 'Basic Research and Applied Research' method. The results of this study show: First, there are 34 points of conceptual actions successfully identified from the principles of the Movement on Growing the Budi Pekerti (Character) Base on Multiculturalism, which, practically and theoretically, need to be implemented in primary schools. Secondly, most (21 from 34) of the points of conceptual actions identified from the principles of the Movement on Growing the Budi Pekerti (Character) Base on Multiculturalism, that need to be implemented in primary schools are the points of conceptual action that have been implemented at primary schools, while a few the points of conceptual action other (13 from 34 points) are the points that have not been implemented at primary schools; Thirdly, the points of conceptual action of 'the Movement on Growing The ‘Budi Pekerti’ (Character) Based on Multiculturalism' which have been implemented in primary schools, are basically only implemented by the initiatives of schools, and not specifically based on multiculturalism. Fourthly, certain points of action that have not yet been implemented in primary schools are due to internal factors, that the points of conceptual action have not been programmed by the schools, and due to external factors, namely that there are no any rule or policy that obligate schools to implement them.